Vitamin D supplementation in bacterial vaginosis - T.F. Tatarchuk; L.V. Kalugina; T.I. Kvasha; R.O. Mnevets (Publishing House TRILIST, 2023)
Research objectives: to evaluate the effect of vitamin D supplementation (Olidetrim) in the complex anti-relapse therapy of bacterial vaginosis (BV) in women of reproductive age. Materials and methods. The study included 63 women of reproductive age with BV and with a level of 25-hydroxyvitamin D below 75 nmol/l, who were divided into groups: the main group included 32 women who were prescribed standard therapy (metronidazole 500 mg twice a day for 7 days) and cholecalciferol (Olidetrim) 4000 IU/day with subsequent continuation of its intake in a dose 2000 IU/day for up to 6 months; the comparison group included 31 women, who were not intake vitamin D preparation during the standard therapy and during the next 6 months of observation. After treatment, women provided completed questionnaires and self-collected vaginal swabs 1, 3, and 6 months after beginning of the study or before BV relapse. Evaluation of Gram-stained smears was carried out by microscopy according to Hay/Ison criteria, where BV corresponded to type III. The level of 25-hydroxyvitamin D in blood serum was determined by the chemiluminescent immunoassay method before the start of the study and at 3 and 6 months of follow-up. The primary endpoint was BV recurrence at any post-treatment interval; the patients were offered a second treatment in this case. Results. Vitamin D deficiency at the beginning of the study was detected in 12 (37.5%) patients of the main group and in 13 (41.94%) women of the comparison group, an insufficient level - in 20 (62.5%) patients of the main group and in 58.06% women of the comparison group. Patients complained of pathological vaginal discharge, itching, burning and dyspareunia lasting from 1 week to 2 months. At the seven-day course of basic BV therapy all participants noted the normalization of discharge and the absence of vaginal discomfort. Positive dynamics were also observed according to the gynecological examination. One month after the treatment, 4 (12.5%) participants of the main and 6 (19.36%) women of the comparison group noted the recovery of symptoms. Absence of BV recurrence after 3 months was noted by 25 (78.12%) women of the main group and 16 (51.61%) women of the comparison group (p = 0.054), that was confirmed by the laboratory tests. At the same time, the level of 25-hydroxyvitamin D in the main group increased by 43.37% (p = 0.05), and in the comparison group it did not differ from the initial level. There were no complaints in 24 (75.0%) patients after 6 months, however, a laboratory-confirmed normal state of the vaginal microbiome was observed in 22 (70.96%) participants of the main group and in 14 (45.16%, p = 0.07) women of the comparison group. Continuation of vitamin D intake at a dose of 2000 IU/day for the next 3 months demonstrated maintenance of the 25-hydroxyvitamin D level within normal values (81.7 ± 6.23 nmol/l in the main group vs. 38.51 ± 5.43 nmol/l in comparison group, p = 0.05). Conclusions. A decrease in the frequency of BV recurrences in women during support a normal level of vitamin D was found, which allows recommending the inclusion of cholecalciferol supplementation (Olidetrim) in the standard treatment. In patients with recurrent BV a long-term monitoring of the serum level of vitamin D is advisable in order to timely prescribe supplementation.